Duchenne and Becker muscular dystrophy: a molecular and immunohistochemical approach Distrofia muscular de Duchenne e Becker: abordagem molecular e imuno-histoquímica - Aline Andrade Freund; Rosana Herminia Scola; Raquel Cristina Arndt; Paulo José Lorenzoni; Claudia Kamoy Kay; Lineu Cesar Werneck (Arquivos de Neuro-Psiquiatria)
Duchenne muscular dystrophy (DMD) and Becker muscular dystrophy (BMD) are caused by mutations in the dystrophin gene. We studied 106 patients with a diagnosis of probable DMD/BMD by analyzing 20 exons of the dystrophin gene in their blood and, in some of the cases, by immunohistochemical assays for dystrophin in muscle biopsies. In 71.7% of the patients, deletions were found in at least one of the exons; 68% of these deletions were in the hot-spot 3' region. Deletions were found in 81.5% of the DMD cases and in all the BMD cases. The cases without deletions, which included the only woman in the study with DMD, had dystrophin deficiency. The symptomatic female carriers had no deletions but had abnormal dystrophin distribution in the sarcolemma (discontinuous immunostains). The following diagnoses were made for the remaining cases without deletions with the aid of a muscle biopsy: spinal muscular atrophy, congenital myopathy; sarcoglycan deficiency and unclassified limb-girdle muscular dystrophy. Dystrophin analysis by immunohistochemistry continues to be the most specific method for diagnosis of DMD/BMD and should be used when no exon deletions are found in the dystrophin gene in the blood. As distrofias musculares de Duchenne (DMD) e de Becker (DMB) são doenças causadas por mutação no gene da distrofina. Foram estudados 106 casos com a suspeita diagnóstica de DMD/BMD com a analise de 20 exons do gene da distrofina no sangue e biópsia muscular com imuno-histoquímica para distrofina em alguns casos. Em 71,7% dos casos foi encontrada deleção em pelo menos um dos exons, sendo que 68% das deleções localizam-se na região 3' hot spot. Foram encontradas deleções em 81,5% dos DMD e em todos os BMD, sendo que os sem deleção tinham deficiência de distrofina, incluindo a mulher com DMD. As portadoras sintomáticas não tinham deleções mas anormalidades na distribuição da distrofina no sarcolema. Os outros casos sem deleção, com auxilio da biópsia muscular tiveram outros diagnósticos (atrofia muscular espinhal, miopatia congênita, deficiência de sarcoglicanos, distrofia de cinturas-membros sem classificação). A análise imuno-histoquímica para distrofina na biópsia muscular continua sendo o método mais específico para diagnóstico de DMD/DMB e deve ser utilizado quando não são encontradas deleções do gene da distrophina no sangue.